A method to simultaneously construct up to 12 differently sized Illumina Nextera long mate pair libraries with reduced DNA input, time, and cost. (July 2015) - Heavens, Darren; Accinelli, Gonzalo Garcia; Clavijo, Bernardo; Clark, Matthew Derek
Long mate pair (LMP) or "jump" libraries are invaluable for producing contiguous genome assemblies and assessing structural variation. However the consistent production of high quality (low duplication rate, accurately sized) LMP libraries has proven problematic in many genome projects. Input DNA length and quantity are key issues that can affect success. Here we demonstrate how 12 libraries covering a wide range of jump sizes can be constructed from <10 µg of DNA, thus ensuring production of the best LMP libraries from a given DNA sample. Finally, we demonstrate the accuracy of the insert sizes by mapping reads from each library back to an existing assembly.